Teaching Practices Promoting Communication Opportunities in the Language Class - Samuel S. Poliden (Philippine Association of Institutions for Research, Inc., 2012)
The study investigated the teaching practices that promote communication opportunities in the language class. Four teaching practices, six language functions and preferred error correction method were observed, recorded and analyzed using weighted means, frequency counts, percentages, ranks and the Cochran Q-test. Findings revealed that building on prior knowledge and communitarian teachings were predominantly used followed by multiple representations and protracted language event, the least. Eliciting, on the other hand was commonly used by the English teachers in engaging the students in classroom proceedings followed by evaluating, sociating, directing and organizing. The most preferred methods of correcting errors were for the teacher to point out the error and provide the correct form; and to explain why the utterance is incorrect. The study showed that teachers use varied teaching practices to provide communication opportunities for students. The study recommends that: (1) the use of multiple representations and protracted language event should also be utilized by teachers to provide students with varied activities and to develop with confidence their communication skills; (2) Activities given to students should be more challenging to encourage them to ask questions that develop their critical thinking; 3) Teachers should adopt more implicit error identification techniques for students to reflect on and repair their own errors.